Stato civile e cultura politica islamica. Una riflessione antropologica - Domenico Copertino (Archivio Antropologico Mediterraneo)
Starting from the debate between Clifford Geertz, Talal Asad and Ernest Gellner on religious traditions, ethos and power, the article offers a reflection on the political-intellectual dynamics that have led some Islamic and secular movements in the Middle East to formulate a project of social/institutional organization called the civil state. The debate on this form of state lasted over a century and returned to the center of Islamic public discourse after the revolutions of 2010/2011. The article investigates the historical-political circumstances and the power/authority relations through which the model of the civil state was developed and adapted by the contemporary Islamic public, particularly in Egypt and Tunisia.